Administrative-legal basis of the psychological service activity of modern university - Furman, Anatolii; Nadvynychna, Tetiana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article discloses the administrative-legal basis, principles and norms of thepsychological service activity of a university.The exceptionally important place and constructive role of this structural unit in the educational space of a modern institution of higher education isproved, which provides conditionsthat contribute to professional developmentand personal growth of students, their psychological security, strengthening of psycho-spiritual health,the creation of favorable socio-psychological conditions for the implementation of educational activity and self-organization. The normative base, which regulates an activity of PSU (psychological service of university) and changes, additions at the legislative level that were introduced to it, are analyzed.It is noted that modern psychological service is an integral part of a successful functioning of modern HEI (higher education institution) as a scientific-educational institution of innovative direction.